THE EFFECT OF DIFFERENTIATION AND PROMOTION TOYOTA AVANZA PURCHASING DECISION IN PT. NASMOCO PEMUDA SEMARANG - Adityan Dwi Purnomo; Sudharto Prawata Hadi; Bulan Prabawani (Universitas Diponegoro, 2015)
PT. Nasmoco Pemuda Semarang is a company engaged in the marketing of Toyota products for Central Java and Yogyakarta. The tied competition of automotive business led to decreased supposed to be adjective in the number of buyers and many new products from Toyota competitors sells new products with a more elegant design and reasonable price. This study is aimed to identify the driving factors of purchase decisions, specifically differentiation (X1) and promotion (X2) factor on purchasing decision (Y) in PT. Nasmoco Pemuda Semarang. The research type employed is explanatory research. The population used is the consumers buying Toyota Avanza in PT. Nasmoco Pemuda Semarang. The sample used in this study were 98 respondents calculated using the formula Slovin. The sampling technique uses accidental sampling technique. Instrument data collection technique are in questionnaires and interviews. Data were analyzed using linear regression analysis. This research concludes that the differentiation and promotion have an influence on purchasing decisions. Differentiation and promotion explained the purchase decision variable at 24.8% where differentiation has the effect of 26.1% and 15.1% promotion. Differentiation and promotion has significant effect on the purchase decision in PT. Nasmoco Pemuda Semarang, where differentiation has the highest influence. PT. Nasmoco Pemuda Semarang are suggested to frequently conduct sales promotions and provide discount that can make consumers interested to buy Toyota Avanza. Beside that, it’s suggest that PT. Nasmoco Pemuda Semarang increasing personal selling’s aspects and direct marketing so that consumers knew the product of Toyota Avanza.